Efektivitas Pembelajaran Matematika Menggunakan Multimedia pada Materi Kerucut - Prasetyo Usman; Lailany Yahya; Nursiya Bito; Bertu Rianto Takaendengan (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
This is descriptive research which aims to describe the effectiveness of learning by using multimedia in the cone materials of class IX MTs Al-Khairat Kwandang in the academic year 2019/2020 in terms of (1) the ability of teachers to manage learning, (2) positive student responses to learning, and (3) student learning outcomes test. Based on the analysis and discussion results, it can be concluded that learning mathematics using multimedia on cone material is effective. This is indicated by the ability of teachers to manage to learn has been categorized as very good, student responses in every aspect during the learning process are categorized as very positive, and the completeness of learning outcomes has reached 80% classically.